Compression and Wear Properties of Biocompatible Commercially Pure Titanium and (Titanium-Silicon) Alloys - Al-Hassania, Emad S.; Dawood, Jamal J.; Al-Sabe’a, Balsam M. (Anbar Journal of Engineering Sciences, 2019)
The porous Titanium is characterized by high permeability which can assure the ingrowth of bone tissues, and consequently results in a good bonding between the metallic implant and the bone. In this work, Silicon element was added to the Commercially Pure Titanium at different weight percent of (2, 4, 6, 8 and 10) to investigate its effect on the porosity percentage, mechanical properties of the resulted samples. XRD analysis stated that at (Si) content lower than (2 wt%) the alloy is single phase (α- Ti alloy), as the Silicon content increased, in addition to (αphase), (Ti5Si3) intermetallic compound developed in the alloy. Porosity measurement results showed that the porosity percentage increases with the increase in Silicon content. Wear results stated that the wear rate increases with the increase in silicon content due to the increase in porosity percentage while the hardness results stated that there is no significant effect for Ti5Si3 intermetallic compound on improving the hardness of the samples. This is attributed to its low percent and the major effect of porosity on hardness which declined the effect of Ti5Si3 by reducing the hardness of the alloy compared with the master sample. The obtained results of the (yield strength, ultimate compressive strength and Young’s modulus) were within the values that match bone’s properties. This means these materials are suitable for biomedical application